LITERASI AKUNTANSI SYARIAH PADA PELAKU UMKM: STUDI FENOMENOLOGIS - Kholifatus Syaadah; Nurbayanti, Nishfu; Fauzia, Syifa; Ananda, Dea (Jurnal Liga Ilmu Serantau, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the national economy, yet they still face limitations in financial management, particularly related to sharia accounting literacy. The lack of technical understanding and dominance of normative interpretations cause sharia accounting principles to not be applied systematically in MSME financial recording practices. This research aims to deeply understand the experiences and interpretations of MSME actors regarding sharia accounting literacy in business financial management. This research uses a qualitative approach with a phenomenological method through in-depth interviews with MSME actors. The research results show that sharia accounting is more understood as moral and ethical business values, such as honesty and avoiding usury, rather than as a formal financial recording system. The conclusion of this research affirms the existence of a gap between values and practices, thus requiring guidance and practical sharia accounting education tailored to MSME characteristics, as well as the development of contextual mentoring models so that sharia principles can be applied sustainably in daily business activities and decision-making.